A Structure Equation Model Examining Self-care Behavior toward Pregnancy-related Complication and Their Associated Factors among Women in Indonesia - Nurhasanah, Rika; Masrul, Masrul; Malini, Hema; Tarawan, Vita Murniati (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Maternal mortality rate is commonly caused by pregnancy-related complications. Performing adequate self-care could reduce maternal and child mortality, improve quality of life, and reduce health-care expenses. Few studies exploring factors associated with self-care behaviors toward pregnancy-related complications using the basis of Orem’s theory. AIM: This study aimed to investigate the self-care behaviors pregnancy-related complications and their associated factors among women in Indonesia. METHOD: This study was used a cross-sectional design. A multistage random sampling of 320 pregnant women was recruited from four Public Health Centre in West Java, Indonesia. Participants were 18 years old or older and trimester II and III. Structural equation modeling was used for analysis. RESULTS: The mean age of the mother was 27 years (SD = 6.03) and gestational age was 26 months (SD = 9.17). A pregnant woman has moderate self-care behaviors with a mean of 156.5 (SD = 16.91). Path analysis revealed that knowledge, self-efficacy, and social support have both direct and indirect effects through empowerment on self-care behaviors toward pregnancy-related complications. CONCLUSION: This finding provides an initial understanding of basic conditioning factors on self-care behaviors and the mediating role of empowerment. This study also provides a significant contribution for clinical practice as basic data to establish future intervention to promote empowerment to achieve optimal self-care behaviors in pregnant women to prevent a complication.